2011
DOI: 10.1016/j.regpep.2011.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Biological and conformational evaluation of angiotensin II lactam bridge containing analogues

Abstract: Angiotensin II (AII) is the active octapeptide product of the renin enzymatic cascade, which is responsible for sustaining blood pressure. In an attempt to establish the AII-receptor-bound conformation of this octapeptide, we designed conformationally constrained analogues by scanning the entire AII sequence with an i-(i+2) and i-(i+3) lactam bridge consisting of an Asp-(Xaa)(n)-Lys scaffold. Most analogues presented low agonistic activity when compared to AII in the different bioassays tested. The exceptions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Peptides were cleaved and deprotected in anhydrous hydrogen fluoride (HF) and purified by RP-HPLC. Analysis by RP-HPLC and capillary electrophoresis (CE) revealed that the purity of all synthesized compounds exceeded 96% [32]. Peptides were characterized by an amino acid analysis and LC/ESI(+)-MS. Figure 1 shows the anti-plasmodium activity of the AII analogs as quantitated by the fluorescence microscopy.…”
Section: Membrane Permeability Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Peptides were cleaved and deprotected in anhydrous hydrogen fluoride (HF) and purified by RP-HPLC. Analysis by RP-HPLC and capillary electrophoresis (CE) revealed that the purity of all synthesized compounds exceeded 96% [32]. Peptides were characterized by an amino acid analysis and LC/ESI(+)-MS. Figure 1 shows the anti-plasmodium activity of the AII analogs as quantitated by the fluorescence microscopy.…”
Section: Membrane Permeability Assaymentioning
confidence: 99%
“…This fundamental limitation of AII highlights the necessity for the derivation and synthesis of new compounds based on its structure that maintain its anti‐malarial effects while eliminating its biological effects on humans. Several AII analogs were synthesized with two modified N ‐terminal amino acid residues (Asp and Lys), resulting in the intramolecular formation of lactam bridges and the induction of a structural folding that increases the ability of these antimicrobial peptides to disrupt the lipid membranes of plasmodia . To determine how these lactam bridges enhance anti‐malarial activity, we synthesized the corresponding linear peptides – without lactam bridges.…”
Section: Introductionmentioning
confidence: 99%
“…The cyclic analogs were able to inhibit approximately 75% of the sporozoites population, and the linear analogs promoted a decrease between 67% and 87%. Importantly, these analogs did not exhibit effects on blood pressure .…”
Section: Introductionmentioning
confidence: 97%
“…In an attempt to reduce the degree of conformation freedom, 21,22 we designed conformationally constrained analogues by scanning the residues 3, 6, 7, and 10 important for the biological activity of I-4 while the other residues were left unchanged with the i − (i + 2) lactam bridge consisting of a Glu-Xaa-Lys scaffold.…”
Section: Oral Glucose Tolerance Tests (Ogtts) Of Ii-1-4 Evaluated In mentioning
confidence: 99%